Efficient ambient-air-stable solar cells with 2D–3D heterostructured butylammonium-caesium-formamidinium lead halide perovskites - Wang, Z; Lin, Q; Chmiel, F; Sakai, N; Herz, L; Snaith, H (Springer Nature, 2017)
Perovskite solar cells are remarkably efficient; however, they are prone to degradation in water, oxygen and ultraviolet light. Cation engineering in 3D perovskite absorbers has led to reduced degradation. Alternatively, 2D Ruddlesden–Popper layered perovskites exhibit improved stability, but have not delivered efficient solar cells so far. Here, we introduce n-butylammonium cations into a mixed-cation lead mixed-halide FA0.83Cs0.17Pb(IyBr1−y)3 3D perovskite. We observe the formation of 2D perovskite platelets, interspersed between highly orientated 3D perovskite grains, which suppress non-radiative charge recombination. We investigate the relationship between thin-film composition, crystal alignment and device performance. Solar cells with an optimal butylammonium content exhibit average stabilized power conversion efficiency of 17.5 ± 1.3% with a 1.61-eV-bandgap perovskite and 15.8 ± 0.8% with a 1.72-eV-bandgap perovskite. The stability under simulated sunlight is also enhanced. Cells sustain 80% of their ‘post burn-in’ efficiency after 1,000 h in air, and close to 4,000 h when encapsulated.